2021
DOI: 10.1038/s41598-021-91535-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral leucocyte molecular indicators of inflammation and oxidative stress are altered in dairy cows with embryonic loss

Abstract: Objective of experiment was to determine whether oxidative stress (OS) and inflammation altered embryonic loss in dairy cows. Blood samples were collected at days 0, 16, 32 and 60 after timed (AI) from 200 Holstein cows to determine embryonic loss based on interferon-stimulated gene-15 (ISG15) mRNA expression (day 16) and ultrasound at day 32 and day 60. Leucocyte expressions of mRNA TLR2, TLR4, TNF-α, IL1B, IL10, STAT3 (inflammation), PTGS2, PTGES (prostaglandin synthesis), and PLA2G4A and ALOX5AP (eicosanoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The relatively greater values of TBARS and AOPP in cows with early embryonic loss are indicative of oxidative damage of lipids (TBARS) and proteins (AOPP) ( Figure 1 ). Similar results were described by Dirandeh et al (2021) [ 3 ] reporting decreased total antioxidant capacity (TAC), SOD and GPx in cows with embryonic loss, as well as increased lipid peroxidation. Zhao et al (2019) [ 35 ] reported that GPx abundance was greater in cyclic cows compared to cows with inactive ovaries, suggesting that OS in ovaries may lead to failure in follicular development to form a cumulus structure that promotes oocyte production.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The relatively greater values of TBARS and AOPP in cows with early embryonic loss are indicative of oxidative damage of lipids (TBARS) and proteins (AOPP) ( Figure 1 ). Similar results were described by Dirandeh et al (2021) [ 3 ] reporting decreased total antioxidant capacity (TAC), SOD and GPx in cows with embryonic loss, as well as increased lipid peroxidation. Zhao et al (2019) [ 35 ] reported that GPx abundance was greater in cyclic cows compared to cows with inactive ovaries, suggesting that OS in ovaries may lead to failure in follicular development to form a cumulus structure that promotes oocyte production.…”
Section: Discussionsupporting
confidence: 89%
“…Pregnancy status at day 16 after TAI was predicted via blood cell ISG15 mRNA gene expression. Prediction of pregnancy was based on blood cellular ISG15 expression greater than −7.0 at day 16 after TAI [ 3 , 21 ]. Pregnancy at day 32 after TAI was diagnosed via transrectal ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations